IMPLEMENTASI METODE SCRUM PADA WEBSITE PENDAFTARAN PASIEN RAWAT JALAN - Nurhayati; Sri Wahyuningsih Nugraheni (Nusantara Hasana Journal, 2023)
Websites in health services are expected to be able to manage information and data processing to be faster and according to minimum service standards. This study aims to develop an outpatient registration website by applying the Scrum system development method. The research method used is descriptive research including data collection and software requirements analysis, website modeling and website development using the Scrum model. The website is developed using PHP and Mysql. This research was able to produce an outpatient registration website, the scrum method was able to make website work more effective, efficient and structured.